(untitled) (International Journal of Food and Nutritional Sciences, 2023)
Aim: The aim of the present study was to study the efficacy of Dashmoola taila abhyang followed by Dashamoola kwath nadi swedan in the management of Manyasthambha. Material and Method: Our clinical study was performed on 69 patients in the Panchakarma Out Patient Department. Dashmoola taila abhyanga was applied followed by Dashmoola kwath nadi swedan for the management of Manystambh which described in Shirorogadhikar Adhayay in Bhaiysaijya Ratnavalli. The Visual Analog Scale (VAS), Goniometric Measurements, Manyashoola (Neck Pain), Stambha (Stiffness) were the criteria assessed at baseline, one week and two weeks post treatment. Results: The Visual Analog Scale (VAS), Goniometric Measurements, Manyashoola (Neck Pain), Stambha (Stiffness) showed statistically significant reduction in all patients. As per above result of all parameters, treatment is effective in the management of Manyastambha which reveals that, 20% patients shown complete remission, 68% patients shown marked improvement, 12% patients shown moderate improvement. Conclusion: This study concluded that, treatment of Dashmoola taila abhyang followed by nadi swedan shows complete remission and marked improvement i.e., effective in the management of Manyastambha.